2020
DOI: 10.1186/s41927-020-00130-x
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacological and clinical aspects behind dose loading of biological disease modifying anti-rheumatic drugs (bDMARDs) in auto-immune rheumatic diseases (AIRDs): rationale and systematic narrative review of clinical evidence

Abstract: Background Dose loading of biological disease modifying anti-rheumatic drugs (bDMARDs) in auto-immune rheumatic diseases (AIRDs) is performed to achieve steady state drug concentrations earlier after treatment start compared to dosing regimens without loading. Although loading inherently results in increased costs, treatment targets in terms of reduced disease activity may be achieved at an earlier state. It is an interesting topic that, surprisingly, has not received much attention in literature.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…A systematic review on this subject found comparative studies with/without loading doses for abatacept and certolizumab in RA and secukinumab in both PsA and axSpA. 31 The authors concluded that there is insufficient evidence on the superiority of dose loading for these drugs. For the other drugs authorised with a loading dose, no comparative studies were found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review on this subject found comparative studies with/without loading doses for abatacept and certolizumab in RA and secukinumab in both PsA and axSpA. 31 The authors concluded that there is insufficient evidence on the superiority of dose loading for these drugs. For the other drugs authorised with a loading dose, no comparative studies were found.…”
Section: Resultsmentioning
confidence: 99%
“…The task force advocates that a loading dose should not be used when superiority on effectiveness has not been demonstrated in a head-to-head study. A systematic review on this subject found comparative studies with/without loading doses for abatacept and certolizumab in RA and secukinumab in both PsA and axSpA 31. The authors concluded that there is insufficient evidence on the superiority of dose loading for these drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Future studies should consider alternative analytical methods to capture the long-term value of treatments for patients with PsA. Lastly, two limitations related to the treatments in the NMA include: (1) comparisons between intravenous and oral medications, which may have biased the results in favour of intravenous drugs which work more quickly over the first few weeks and (2) comparisons of DMARDs administered using a loading dose to those without a loading dose, which may have introduced variability; however, evidence on the superiority of regimens with loading doses in autoimmune rheumatic diseases is inconclusive 30…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory gastrointestinal diseases, Crohn's disease and ulcerative colitis, required high loading and low maintenance doses, possibly due to loss of protein from inflamed gastrointestinal mucosa. 1 This study identified patterns of loading and maintenance dose use in biologic therapy for inflammatory disease. The pattern of loading dose use seems to cluster in the specialty in which the drug was developed and affects cost and sustained efficacy.…”
Section: Ramentioning
confidence: 99%
“…[2][3][4] Published reasons for loading dose use include the need for more drug to achieve than maintain disease control, to neutralize or prevent the formation of anti-drug antibodies and to achieve therapeutic drug levels in protein-losing enteropathies, like Crohn's disease and ulcerative colitis. 1,5,6 However, there is no clear pattern of biologic therapy use, as regimens with loading doses are recommended for some biologics but not others, sometimes independent of half-life and drug. 1 This study seeks Table 1 FDA-approved biologic therapy regimens by therapy and indication 5,7 Adalimumab PsO/Uveitis: 80 mg initial dose, followed by 40 mg every other wk starting one wk after initial dose PsA/RA/AS: 40 mg every other wk CD/UC/HS: Day 1: 160 mg, day 15: 80 mg, day 29: maintenance 40 mg every other wk Adalimumab-adbm PsO: 80 mg initial dose, followed by 40 mg every other wk starting one wk after initial dose PsA/RA/AS: 40 mg every other wk CD/UC: Day 1: 160 mg, day 15: 80 mg, day 29: maintenance 40 mg every other wk BrodalumabPsO: 210 mg at wks 0, 1 and 2, followed by 210 mg every 2 wks…”
mentioning
confidence: 99%